Does outdoor work during the winter season protect against depression and mood difficulties? - Ina H Hahn; Matias Brødsgaard Grynderup; Sofie B Dalsgaard; Jane Frølund Thomsen; Åse Marie Hansen; Anette Kærgaard; Linda Kærlev; Ole Mors; Reiner Rugulies; Sigurd Mikkelsen; Jens Peter Bonde; Henrik A Kolstad (Nordic Association of Occupational Safety and Health (NOROSH), 2011)
OBJECTIVE: At temperate latitudes, 1-5% of the population suffer from winter depression; during winter, mood difficulties tend to increase but may be alleviated by bright light therapy. Unlike indoor workers, outdoor workers are exposed to therapeutic levels of sunlight during winter. We hypothesized that outdoor work may protect against mood difficulties and depression. METHOD: We studied this hypothesis among 2910 civil servants from Århus, Denmark, who participated in a survey in January-February 2009. Mental symptoms (N=422) defined a common case category that we broke down into two parts: depression (N=66) and mood difficulties but no depression (N=356). A total of 222 controls were also sampled from the study population. All 644 participants reported the extent of outdoor work. RESULTS: The confounder-adjusted odds ratio (OR) of mood difficulties showed a decreasing trend by increasing hours of outdoor work of borderline statistical significance. The OR was 0.63 [95% confidence interval (95% CI) 0.34-1.18)] for those working outdoors for >2 hours a day. No such effect was suggested for depression. CONCLUSION: Our study is limited by its cross-sectional design and low statistical power but nevertheless suggests that outdoor work during winter may protect against mood difficulties. If this finding holds true it may have significant impact on workers' health as well as public health in general. Therefore, further studies are recommended.